Anatomically-based musculoskeletal modeling: prediction and validation of muscle deformation during walking - Oberhofer, K.; Mithraratne, K.; Stott, N. S.; Anderson, I. A. (The Visual Computer, 2009)
Abstract Accurate modeling of the musculoskeletal system during motion is a challenging task that has not yet been solved. In this paper, we outline and validate a free-form deformation method called the Host Mesh Fitting (HMF) technique for predicting muscle deformation during walking of a subject-specific musculoskeletal model. 20 lower limb muscles were deformed according to the HMF solution of a surrounding host mesh that resembled the skin boundary, resulting in a realistic walking simulation of the anatomicallybased model. The shape changes of five muscles were further validated by comparing the predicted deformations with magnetic resonance image data in two lower limb positions.